Sifat Mekanis Beton Kulit Kerang (Anadara Grandis) - Annisa Arifandita Mifshella; Monita Olivia; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This study is to evaluate the mechanical properties namely compressive strength and splitting tensile strength of concrete using clamshell powder as a partial cement substitute. The clamshell powder was made from grinding Anadara grandis shells that were burnt at furnace brick and filtered using no #200 sieve. An initial investigation was carried out to make concrete specimens with partial replacement of shells powder using 2%, 4%, 6% and 8% of the weight of cement. The results of the initial study showed that the optimum clamshell powder proportion to get a high compressive strength was 4%. The specimens for compressive strength and splitting tensile strength were manufactured using 4% clamshell powder as a partial cement substitution. The specimens were tested atthe age of 7, 28, and 91 days. The results showed that the compressive strength of concrete using clamshell powder has lower strength than normal concrete for all age of specimens. On the other hand, the splitting tensile strength of concreteusing clamshell powder was higher than normal concrete.Keyword: clamshell powder, compressive strength, tensile strength, OPC